Environmental management - Water footprint - Illustrative examples on how to apply ISO 14046
ISO/TR 14073:2017 provides illustrative examples of how to apply ISO 14046, in order to assess the water footprint of products, processes and organizations based on life cycle assessment. The examples are presented to demonstrate particular aspects of the application of ISO 14046 and therefore do not present all of the details of an entire water footprint study report as required by ISO 14046.